LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Mozambique plantation leaves no land or jobs for villagers - Adler, Nils (New Internationalist, 2018)
In northern Mozambique, villagers were promised jobs to replace land taken for forestry. Five years later, they’re still waiting, discovers Nils Adler.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

Socio-economic impacts of private land use investment on rural communities: Industrial forest plantations in Niassa, Mozambique - Bleyer, Maja; Kniivilä, Matleena; Horne, Paula; Sitoe, Almeida; Falcão, Mário Paulo (Land Use Policy, 2016)
East Africa has experienced an increase of private land use investments in the past years. Rural households have consequently faced crucial changes in their livelihoods. This paper explores the socio-economic impacts of industrial forest plantations on rural communities in Niassa, Mozambique. According to our results private forest plantations have the potential to positively impact local people’s wealth and well-being, if enough emphasis is given to minimizing the negative impacts. The household survey data of 218 observations from five villages were analyzed using binary and multinomial logistic regression analyses. The study shows that forest plantations have threatened the basis of traditional rural livelihoods by reducing the availability of natural resources and through the relocation of agricultural plots. However, investments have also supported the diversification of livelihood strategies in the communities by providing formal employment and by increasing business and trading activities. As growing population and traditional agricultural practices have led to the overexploitation of natural resources, non-natural resource-based livelihood strategies increase the resilience of a household. The majority of respondents reported plantations to have either no overall impact or a positive impact on the well-being of their household. According to our results, socio-economic household characteristics only marginally explain respondents’ perceptions of the impacts of forest plantations but perceptions differ significantly between individual villages.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Guião de Consultas Comunitárias - Tankar, Issufo (Centro Terra Viva (CTV), 2014)
Em 2009, o Centro Terra Viva (CTV) publicou o Guião de Consultas Comunitárias, como parte do seu esforço em melhorar a aplicação da legislação sobre terras e outros recursos naturais. O guião resultou de várias pesquisas de campo realizadas pelo CTV e outras organizações que trabalham na área de Terras. No entanto, a aprovação do Decreto n° 43/2012 de 10 de Outubro, seguida do Diploma Ministerial n° 158/2011 de 15 de Junho, uma parte significativa do Guião ficou ultrapassada. Por outro lado, foram aprovadas directrizes pelo Fórum de Consulta sobre a Terra que são relacionadas a este tema. Deste modo, e como forma de facilitar a interpretação e aplicação do quadro legal sobre consultas comunitárias, o Centro Terra Viva, produziu este guião de consultas comunitárias destinado às comunidades, técnicos do Estado, técnicos de ONG’s e todos actores que trabalham na área de Terras.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Mozambique land policy development case study - Locke, Anna (Overseas Development Institute, 2014)
This case study has been produced in response to a request made to the Evidence on Demand Helpdesk. The objective of the request was to provide a detailed case study on the evolution of land policy in Mozambique and provide the reader with insights into what is viewed as one of Africa’s most progressive land laws, recognising multiple forms of tenure. Mozambique has experienced accelerated rates of growth over the past decade, averaging 7.2% per year, with projected growth rates of over 8%. However, this high growth rate has failed to translate into significant reductions in poverty and inequality has increased in almost all parts of the country. While growth has been driven by capital-intensive projects, mainly in the extractives sector, agriculture is seen as an important foundation for economic development and there has been a high level of interest in acquiring large tracts of land for investment over the past six years. Mozambique is one the most land-abundant countries in Africa, with around 80 million hectares (has). Currently, only five million hectares are cultivated, mainly by smallholders under rain-fed, traditional systems, and only 3-5% of landholdings are formally registered.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra

Facing the forest entrepreneurs - Healy, Hazel (New Internationalist, 2013)
Communities are scrambling to protect their lands from the tree plantations multiplying across Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra

Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais